2015
DOI: 10.1016/j.alit.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy preceded by contact urticaria due to the same food: Involvement of epicutaneous sensitization in food allergy

Abstract: Epicutaneous sensitization of foods could induce food allergy under occupational cooking and skin-care treatment with foods in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Common causes include fish, shellfish, wheat, other grains, fruits, and vegetables. Patients may present with respiratory allergy (i.e., asthma, allergic rhinitis), anaphylaxis [24, 25], and/or contact urticaria [26, 27]. A history of symptoms occurring predominantly in the work environment is suggestive.…”
Section: Uncommon Food Allergiesmentioning
confidence: 99%
“…Common causes include fish, shellfish, wheat, other grains, fruits, and vegetables. Patients may present with respiratory allergy (i.e., asthma, allergic rhinitis), anaphylaxis [24, 25], and/or contact urticaria [26, 27]. A history of symptoms occurring predominantly in the work environment is suggestive.…”
Section: Uncommon Food Allergiesmentioning
confidence: 99%
“…Histopathological results from the present work showed EC sensitization of mice could induce the above-mentioned skin lesions and pathological changes in the intestines as found in food allergy. Interestingly, skin from orally-sensitized mice showed only atopic inflammatory responses induced by inflammatory cells (Inomata et al 2015). Thus, it may be concluded that food allergy may occur in response to allergen exposure via different routes.…”
Section: Discussionmentioning
confidence: 98%
“…There are cases in the literature where systemic reactions to foods were preceded by CoU in the patient [37]. Inomota et al reviewed 15 patients who developed food allergy after epicutaneous sensitization; all but one of these patients were employed as cooks, bakers, or housekeepers [37]. Vegetables were the most common cause in the cooks and housekeepers.…”
Section: Contact Urticaria To Foodsmentioning
confidence: 99%